Role of impacted cerumen in hearing loss. - Subha, Sethu Thakachy; Raman, Rajagopalan (Mci Medquest Communications Inc, 2006)
We performed a study to determine if cerumen in the ear canal causes significant hearing loss and to ascertain if there is any correlation between the amount of cerumen and the degree of hearing loss. Our study was conducted on 109 ears in 80 patients. The results indicated that impacted cerumen does cause a significant degree of conductive hearing loss. We found no significant correlation between the length of the cerumen plug and the severity of hearing loss. Nor did we find any significant correlation between the presence of impacted cerumen and variables such as age, sex, ethnicity, or affected side.